Cervical glomectomy: treatment of bronchial asthma - Ugarte Artola, Raúl (Cirugía del Uruguay, 2020)
Carotid glomectomy a surgical procedure with a very low mortality rate it- if any - , of scarce morbidity and with no side-effects has opened up hopeful prospects for the relief of patients with sever asthma and/or resistent to whatever medication.